Kritikou k nepojmovému. O Adornově esejistické metodě - Dyčková, Alžběta (Filosoﬁcký časopis)
The goal that the author of this study focuses on is to provide a brief introduction to the issue of language in the work of Theodor W. Adorno and, in this context, to interpret his approach to philosophy through a presentation of his essayistic form. She first presents Adorno’s philosophical views about the nonidentity of reality, thought and concepts, out of which grows his approach to language, and then briefly introduces his concept of constellations, which follows up on the thinking of Walter Benjamin. She then presents individual features of Adorno’s textual method of composing constellations, or essays, that primarily consist in the negation of the traditional philosophical method. The concluding part of the study contains a brief discussion about what Adorno’s essays are trying to represent and how to discern a text that meets Adorno’s requirements for good essays. With this, the author wants to provide an insight into Adorno’s philosophical efforts from the perspective of his textual method and at the same time she would like to help Adorno’s readers better orient themselves as they make their way through his demanding texts.